Investigations of open-shell open-shell interactions - Starkey, T; Starkey, Tony (2007)
This thesis details research undertaken in the investigation of the open-shell open-shell Van der Waals complexes between nitric oxide (NO) and oxygen (O2) and between nitrogen dioxide (NO2 ) and oxygen (O 2 ). The Fourier transform microwave spectroscopy technique was used during the experimental work. Spectra were recorded for a mixture of NO and O2 over the frequency range 7.0 to 18.2 GHz. Detailed ab initio calculations have been performed on the potential energy surface of both NO-O2 and NO2-O2 using Multi-reference Rayleigh Schrodinger Second Order Perturbation Theory. These calculations were performed for the four distinct states of NO-O2, 2A", 4A", 2A' and 4A', and for the two distinct states of NO,sub>2 -O2, 2A and 4A. Predicted rotational spectra have been generated by modelling the systems with a rigid-rotor Hamiltonians. The effective Hamiltonians included the rotational Hamiltonian, ℋrot, fine structure terms and hyperfine structure terms. It was not possible, for rationalizable reasons, to fit the predicted spectra for NO-O2 to the experimental observations. Experimental details, calculation methods and rotational theory are discussed in the main body of the thesis. Predicted spectra, relevant calculations and other data is presented in the appendices.